ANALISIS KOMPARATIF PENGARUH PEMBERIAN KREDIT TERHADAP PROFITABILITAS PADA BANK SYARIAH DAN BANK UMUM - WIDIA NOVITA; UMAR HAMDAN; RASYID UMRIE (JEMBATAN, 2013)
ABSTRACT This Research aim to analyze the effect of granting credit towards profitability in the Syariah Bank and Commercial Bank in Indonesia. Granting credit is shown with the LDR (Loan To Deposit Ratio) and the profitability shown by ROA (Return On Assets). This is important for the bank to analyze some influence to increase the ROA target condition the appropriate of bank and economic situation. The technique of the sample used is purposive of sampling with the selection criteria of Syariah Banks and Commercial Banks which have the financial report of research complete in the period 2009 – 2011. The technique analysis used is linear regression simple by the with test the hypothesis in partial (T-test). The result showed that variable LDR do not influence significantly to ROA on Syariah Bank while LDR variable influence significantly to ROA on Commercial Banks.